2009
DOI: 10.1017/s0022149x08067217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-protein diet onSchistosoma mansonimorphology visualized by morphometry and confocal laser scanning microscopy

Abstract: Previous studies have shown that protein deficiencies can hamper both the course of experimental schistosomiasis and normal development of adult worms. To further investigate this relationship, we compared adult male and female Schistosoma mansoni from malnourished and well-fed mice through morphometric and confocal laser scanning microscopy analysis. Swiss mice were fed protein-deficient diets (8%) and infected subcutaneously with approximately 80 S. mansoni cercariae (BH strain, Brazil). Control mice were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…; Barros et al . ), and the scarcity of host micronutrients also affected nematode development and reduced parasitic burden in experimental models such as hamsters (Held et al . ) or mice (Bourgeois et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Barros et al . ), and the scarcity of host micronutrients also affected nematode development and reduced parasitic burden in experimental models such as hamsters (Held et al . ) or mice (Bourgeois et al .…”
Section: Introductionmentioning
confidence: 97%
“…Vice versa, malnutrition can influence the development of the parasite in its host. In experimental S. mansoni infections, the development of male and female schistosomes has been shown to be impaired in undernourished mice (Oliveira et al 2003;Barros et al 2009), and the scarcity of host micronutrients also affected nematode development and reduced parasitic burden in experimental models such as hamsters (Held et al 2006) or mice (Bourgeois et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, albumin seems to be an additional source of energy supply for adult schistosomes, as recent studies reported on the underdevelopment of both sexes of adult worms in undernourished mice, which were fed on a protein-deficient diet (Neves et al 2001; Barros et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery, Schistosoma mansoni has been the subject of intense investigation, describing the features of adult worm based on light microscopy [9][10][11][12][13] . With the advances in microscopy technology, confocal laser scanning microscopy has become an invaluable tool for helminthology, mainly for schistosomiasis mansoni studies [14][15][16][17][18][19][20] . The present article revisited the S. mansoni specimens first described by Pirajá da Silva in Brazil, using confocal laser scanning microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…A vitelline gland (vitellaria) joined by a short vitelline duct was also observed. It is worth mentioning that these characteristics have been described during the examination of freshly collected worms 15,16,[19][20][21] .…”
mentioning
confidence: 99%